Los conflictos socioambientales derivados de actividades extractivas en Latinoamérica y la Responsabilidad Social Empresarial. (2020)
This study aims to analyze the socio-environmental conflicts derived from extractive activities in Latin America and the impact of Corporate Social Responsibility (CSR) in the extractive sector. The first stage included bibliometrics by authors and countries found in the scientific literature, leading to 69 publications selected for the term 2012-2017; later on, a systematic review of the literature was conducted in SCOPUS and Web of Science, starting from the recollection, organization, analysis, and interpretation of information. The results highlight three types of conflicts: environmental impact, turf wars, and the violation of human rights; these reveal that the relationships between the extractive sector and CRS should be mediated by a balance of interests and the preservation of ecosystems.